Efficacy of Lamellar Keratoplasty with Acellular Porcine Corneal Stroma in Treatment for Infectious Central and Peripheral Corneal Ulcers - Chen Y; Zhang L; Liu Z; Liu Q; Gao M (Dove Medical Press, 2021)
Yingxin Chen, Linlin Zhang, Zhiling Liu, Qiming Liu, Minghong Gao Department of Ophthalmology, General Hospital of Northern Theater Command, Shenyang, People’s Republic of ChinaCorrespondence: Minghong GaoDepartment of Ophthalmology, General Hospital of Northern Theater Command, 83 Wenhua Road, Shenhe District, Shenyang, 110840, People’s Republic of ChinaTel +86-133-5245-9433Email gaominghong88@yeah.netBackground: The aim of this study was to investigate the efficacy of acellular porcine corneal stroma (APCS) transplantation in the treatment of infectious central and peripheral corneal ulcers.Methods: A total of 45 patients with infectious corneal ulcers who had undergone lamellar keratoplasty using APCS grafts were included. Among these, 24 had lesions located near the pupil (infectious central corneal ulcer group) and 21 had lesions located in the limbus or around the cornea (infectious peripheral corneal ulcer group). Efficacy was assessed in terms of best-corrected visual acuity, graft transparency, corneal neovascularization, corneal reepithelialization, survival rate, and postoperative complications.Results: Baseline characteristics showed that poor visual acuity and larger-diameter APCS graft in the infectious central corneal ulcer group were comparable with the infectious peripheral corneal ulcer grouper group (P< 0.05). After lamellar keratoplasty using APCS grafts, no obvious differences were observed in aspects of graft transparency, corneal neovascularization, or survival rate (P> 0.05). Postoperative complications, ie, delayed corneal epithelial healing, rejection episode, recurrence of infection, and graft melting, were not significantly different between the two groups (P> 0.05). Visual acuity in bothgroups had improved significantly at 3 months and 6 months postoperation, respectively.Conclusion: APCS transplantation is safe and efficacious for treating infectious central and peripheral corneal ulcers. Despite its good efficacy, APCS-graft size, implant position, patient indications, and postoperative management should be kept in mind in treatment for infectious corneal ulcers in different locations.Keywords: acellular porcine corneal stroma, lamellar keratoplasty, infectious central corneal ulcers, infectious peripheral corneal ulcers